DEVELOPING PISA-BASED READING MATERIALS IN INDONESIAN CONTEXT IN THE FORM OF CONTINUOUS TEXT - Selvina, Dita; Inderawati, Rita; Vianty, Machdalena (Sriwijaya University Learning and Education International Conference, 2018)
The aim of this study was to develop PISA-based reading materials in Indonesian context in the form of continuous text. The subject of this study was tenth grade students at SMA N 1 Belitang. The procedure of the study consisted of three stages such as analysis, design, and evaluation. Instructional materials, students' need, learning environmental, and students' reading level were analyzed. The results of the analysis became the basis for designing the product development. Formative evaluation was conducted to see the validity, practicality, and whether or not the developed product had potential effect to the students. Validity was evaluated in expert review phase for its content, instructional design, and language. The product was stated to be very highly valid (3.5). The practicality was evaluated in one-to-one evaluation and small group phases. The results showed that the product was highly practical since the average score in both phases were 2.7 and 2.8, respectively. Field test phase aimed to evaluate whether or not the develop product had potential effect. The judgment of potential effect was seen from the mean score of the students in the field test. The results showed that the average score of the English version was 78 and the average score of Bahasa Indonesia version was 83. It means that PISA-based reading materials in Indonesian context in the form of continuous text was categorized as very had high potential effect to the students.